Aplicação de "tufito" e NPK na adubação do feijão, em um solo de Patos de Minas - Ferreira de Novais , Roberto; Julião Braga Filho, Luiz (Revista Ceres, 2025)
The aim ofthis experiment was to study the use of "tufito" (deposit of volcanic lava and ashes) in fertilizing the soils of Patos de Minas and to obtain information about the application of N-P-K on these soil in the production of edible beans.